Dry matter production and radiation use efficiency of pulses grown under different light conditions (Bangladesh Journal of Botany, 2019)
A field experiment was conducted to determine the effects of varying light conditions on growth, morphology and seed yield of pulses. Treatments consisted of 50, 75 and 100% of the full sunlight tested in pigeonpea, cowpea, lablab and blackgram species. Under field condition, artificial shade was created by erecting white nylon nets at 30 days and maintained until final harvest. Results showed that shading at both 50 and 75% of the full sunlight had significant (p < 0.05) negative effect on leaf area index (16 - 35%), total dry matter production (11 - 18%), grain yield (19 - 32%) of pulses over full sunlight. However, radiation use efficiency (RUE) of pulses based on either grain or biomass production was higher in shade plants. Pigeonpea and lablab were relatively shade tolerant compared to cowpea and blackgram with potential crops for growth under reduced light environment conditions.